2021
DOI: 10.15446/rfnam.v74n1.88835
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of winter wheat (Triticum aestivum L.) grain in relation to nitrogen fertilization

Abstract: Winter wheat is commonly cultivated in Ukraine. This crop has nutritional requirements that have been affected due to the climate changes that in the recent years the country has been suffered. In the spring season, the plant is found in growing stage, which requires a suitable nitrogen nutrition and it must be supplied due to the deficit of this element during the vegetative development. Within this framework, this study aimed to establish the optimal nitrogen rate for winter wheat that was applied in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
2
7
0
1
Order By: Relevance
“…itionally, the effectiveness of foliar fertilizers depends on other factors, such as ther or forecrop. Tsvey et al [7] found that spring fertilization was the most important winter wheat. The highest grain yield (6.90 t•ha −1…”
Section: Variant Of Foliar Fertilization Development Phase (Scale Bbc...mentioning
confidence: 99%
See 1 more Smart Citation
“…itionally, the effectiveness of foliar fertilizers depends on other factors, such as ther or forecrop. Tsvey et al [7] found that spring fertilization was the most important winter wheat. The highest grain yield (6.90 t•ha −1…”
Section: Variant Of Foliar Fertilization Development Phase (Scale Bbc...mentioning
confidence: 99%
“…ess of foliar fertilizers depends on other factors, such as t al. [7] found that spring fertilization was the most important t grain yield (6.90 t•ha −1…”
Section: Riant Of Foliar Fertilizationmentioning
confidence: 99%
“…The interaction of productivity factors contributed to the formation of winter wheat grain yield, mainly the number of productive straws formed, the weight of 1,000 grains, the size, and weight of the grain in the ear (Tsvey et al, 2021). Studies of the main indicators for determining the structure of winter wheat crops show that under the influence of mineral fertilisers, the number of productive stems increases (Table 3).…”
Section: Source: Developed By the Authors Of This Studymentioning
confidence: 99%
“…Growth processes, development of vegetative and reproductive organs are largely determined by providing plants with moisture and nutrients. It is known that there is a direct relationship between the yield, vegetative mass and height of plants, since stems and leaves are organs of transportation of mineral and organic substances [5].…”
Section: Introductionmentioning
confidence: 99%